PENGARUH PEMBERIAN AIR KELAPA DAN AIR REBUSAN DAUN SIRIH TERHADAP BUNGA POTONG KRISAN (Chrysanthemum,sp) - Inggrit Z. Tuwaidan; Jemmy Najoan; Jeanne M. Paulus (Universitas Sam Ratulangi, 2018)
ABSTRACT The effect of giving coconut water and piper betle decoction water of krisan cutting flower under the guidance of Ir. Jemmy Najoan, MS and Prof. Dr. Ir. Jeanne M. Paulus, MS. The purpose of this study was to determine the interaction between the supply of coconut water and piper betle decoction water to the flower of Krisan, to find out the effect of giving coconut water to Krisan cut flowers, and to determine the duration piper betle decoction water of Krisan cut flowers 20.25 minutes) with variables observed, namely the weight of Krisan cut flowers, stem diameter of Krisan cut flowers, diameter of cut flowers of Krisan and solution absorbed byÂ Krisan cut flowers. This research was conducted at the Plant Sciences Laboratory of the Faculty of Agriculture, Sam Ratulangi University, Manado for 2 months, namely in June - August 2016 with the results of research on giving young coconut water to the weight of Krisan cut flowers producing the highest value of 16,281 and old coconut water 8,750 g , with the highest value on the administration of piper betle boiled water which is in stew for 5 minutes 12,624 followed by stew for 10 minutes 11,423 g and the lowest for the length of stew for 25 minutes 8019 g. Adding the highest stem diameter to the giving of young coconut water 3,100 mm and old coconut water 2,280 mm, while the addition of boiled water piper betle on stew for 5 minutes 2,889 mm and the lowest on stew for 25 minutes 1,878 mm. The highest addition of Krisan cut flower diameter on the addition of young coconut water 2.207 cm and old coconut water 1.410 cm while the highest value in giving piper betle for 5 minutes 1.729 cm. The highest absorbed Krisan solution was given by giving young coconut water 228,692 ml, old coconut water 88,292 ml added boiled water of piper betle to the absorbed solution in stew for 25 minutes 261,736 and the lowest on boiling water for 5 minutes 202,958 ml. Keywords: Coconut Water, Piper Betle Decoction Water, Krisan cutting flower